Development of the Hybrid Training Model by Using Active Learning Methods for Enhancing Specific Competencies of Psychiatric Social Workers - Opaswattana, Chidchanok; Gornnum, Sankamon; Wuttiharn, Phopthorn (Interdisciplinary Academic and Research Journal, 2023)
Active learning process is a student-centered learning management process, emphasizing the role and participation of the learners, by allowing learners to learn and perform activities on their own, which teachers give advice, encourage or facilitate learners to learn through analytical thinking processes, synthesizing learning exchanges between learners and presenting information. The objectives are 1) To develop the hybrid training model by using active learning methods for enhancing specific competencies of psychiatric social workers and 2) To study results by using the hybrid training model by using active learning methods for enhancing specific competencies of psychiatric social workers. Methods: Phase 1 Developing and examining the hybrid training model by using active learning methods for enhancing specific competencies of psychiatric social workers Phase 2 Evaluating the hybrid training model by using active learning methods for enhancing specific competencies of psychiatric social workers. The sample group was 38 social workers who applied the training model willingly. The research tools 1) The hybrid training model by using active learning methods for enhancing specific competencies of psychiatric social workers 2) The specific competencies of psychiatric social work evaluation form 3) The question guidelines to run the focus group for the training model evaluation 4) The evaluation forms for post-training practices of the samples. The data analysis Quantitative data analysis using percentages means, and standard deviations. Qualitative data analysis using content analysis. Results: (A) The hybrid training model using active learning methods consists of (1) Principles (2) Objectives (3) Structures and contents (4) Lesson Plan (5) Learning media (6) Evaluation. The training model runs accordingly through 60–hr, 6 – online modules and 30-hr,1- onsite modules. The hybrid training model and quality content are suitable for all components. which has an index of conformity (IOC) equal to 1.00. (B) Specific competencies evaluation of the sample group shows that mean of pre-training evaluation results of all 3 aspects of the competencies (a. realizing the value, ethics, and standard of psychiatric social work practices; b. Psychiatric social working abilities; c. abilities to develop state of the arts of psychiatric social work) are significantly higher (p < 0.05) than that of post-training ones. And (C) The post-training practices of the sample evaluation show that the training model is suitable, and able to reach many targets such as good working practice attitudes; enhancing knowledge, specific skills, and experiences, ensuring that are applicable for daily practices and improvement networks of psychiatric social workers also.